Doctor as Medicine: Psychological Aspects - A. F. Sokol (Сеченовский вестник)
From positions of cognitive and social psychology influence of the identity of the doctor on health and a course of disease of the patient is considered. At the heart of work the concept of the Nobel Prize laureate D. Kahneman is put. Two types of cogitative activity of the person are discussed (System 1 and System 2). The evaluation of the physicians the patient is provided by System 1. Advantages and shortcomings of System1cognitive mistakes of patients are considered.